The condition of producing homogeneous nanoscale resistive Ni-Ti films by magnetron sputtering from two sources - Valery Vasilev; Alexander Khoshev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the work is caused by the necessity to form nanoscale resistive Ni-Ti films with reproducible parameters for being used in measuring devices operating at high temperatures. The main aim of the study is to prove the opportunities, to define the conditions and modes of producing nanoscale resistive Ni-Ti films with reproducible parameters by magnetron sputtering from two sources for their use in measuring instruments. The methods used in the study: the main principles of thin films physics, magnetron sputtering theory, the theory of the experiment. The results: The paper introduces the comparative evaluation of vacuum thermal evaporation method and magnetron sputtering method, shows the advantages of the latter in formation of metallic thin films of complex composition; introduces the analysis of the state of research in the field of developing nanoscale resistive films for measuring instruments; demonstrates the potential of researching Ni-Ti film and the process for their preparation using the method of magnetron sputtering. The author have proved the possibility, defined the conditions and procedure of obtaining nanoscale resistive Ni-Ti films with reproducible parameters by magnetron sputtering from two sources. It was ascertained that while maintaining a certain ratio of currents density on Ni and Ti targets it is possible to ensure the uniformity and reproducibility of the parameters of nanoscale resistive films (electrical resistivity, TCR). The authors determined that to provide the same speed of sputtering Ni and Ti targets the magnetron current density on Ni target should be 1,67 times higher than magnetron current density on Ti target. Nanoscale resistive Ni-Ti films obtained on glass-ceramic substrates at the specified ratio of magnetron currents densities on the targets had a value of temperature resistance coefficient of ~10-5 °C-1 (in the temperature range from minus 70 to 200 °C). The research materials can serve as the basis for developing new resistive elements of measuring instruments (pressure, force, acceleration sensors, etc.) with improved technical characteristics, operating in conditions of high temperatures.